Determining the components and activity of DNA double-strand break repair pathways in the filamentous fungus Magnaporthe oryzae - McAnany, Tomas (Kansas State University, 2024)
Magnaporthe oryzae, the causal agent of rice blast disease, is an important model pathogen given its worldwide distribution, threat to agriculture across a range of monocot hosts, and varied aggressiveness among strains. While significant progress has been made in understanding the genetics of host-range and virulence, it is still unclear what mechanisms give rise to novel DNA variation given M. oryzae’s mainly asexual reproduction. Previous research from our lab and others indicates that at least four DNA double strand break (DSB) repair pathways are active in M. oryzae, including classical non-homologous end joining (NHEJ), microhomology-mediated end joining (MMEJ), single-strand annealing (SSA), and homologous recombination (HR). While DNA DSB repair is well studied in some eukaryotes, mainly mammals and yeasts, there is not a full description of the genetic requirements, and most importantly, the DNA DSB repair outcomes for each repair pathway in filamentous fungi, especially related to MMEJ and SSA. In this study we utilized a reverse genetics approach to identify the genetic requirements of previously characterized eukaryotic DNA DSB repair homologs, through the creation of gene deletion strains and characterizing repair outcomes in these genetic mutants. By disabling DNA end-resection at DSB sites in ∆mre11, we determined that NHEJ repair resulted in mainly small INDELs that caused deletions of less than 9 base pairs (bp) and insertions of fewer than 5 bp, used minimal microhomology (MH) for repair, included tandem duplications in ~35% of repairs, and resulted in only a single deletion greater than 15 bp. Conversely, by disabling NHEJ and long-range end-resection mediated by Exo1, we specifically identified an MMEJ-like repair profile with much larger INDELs that ranged from -145 bp to -21 bp, and used longer MH, 3 bp to 6 bp, during repair. This study further investigated the genetic requirements of the individual DNA DSB repair pathways in M. oryzae. Deletion of Mre11 impaired end-resection, highlighting its vital role in homology-based repair mechanisms. Hypersensitivity of ∆mre11 to genotoxins confirmed Mre11’s role in end-resection based repair, while insensitivity of ∆ku80 to the tested genotoxins indicated that NHEJ was dispensable for repair of induced DSB. The absence of MMEJ repair in the Δpol4 repair profiles indicated Pol4’s function as an MMEJ polymerase. Lig4 was shown to be crucial for NHEJ, as Δlig4 showed increased end-resection- based repair compared to WT. These findings underscore the essential roles of Mre11, Pol4, and Lig4 in their respective DSB repair pathways as well as provide the foundations for continued research into the DNA DSB repair pathways of M. oryzae.
Keywords: DNA repair; Molecular biology; CRISPR-Cas; Magnaporthe oryzae; Genetics